STUDI KELAYAKAN PENGEMBANGAN GALANGAN KAPAL BARU PT XYZ LOMBOK DENGAN PEMBANGUNAN GRAVING DOCK DITINJAU DARI ASPEK TEKNIS DAN EKONOMIS - Talentha Nursetiandaru (2023)
NTB is one of the ten priority tourism lists that have been released by the Indonesian Ministry of Tourism. It is known that the number of passenger ships operating in NTB is increasing every year. Passenger ships must dock annually. One of the shipyard companies in NTB, PT XYZ Lombok, wants to adjust to the market conditions in the area and the management of PT XYZ Lombok plans to build a graving dock and other additional facilities with the aim of increasing revenue and profits for the company. The method used is an approach based on field production operations to determine workshops and other facilities. To determine the area of workshops and other supporting facilities, a numerical method is used. The design drawing process uses AutoCAD 2017 software and the investment feasibility method is calculated using the investment cost parameters, net cash flow, NPV, IRR, payback period and break event point. So that the area of the shipyard which was previously 47,360 m2 becomes 48,360 m2 after the additional area. The investment cost required for the development of this shipyard is IDR 25,000,000,000 and annual operational costs are IDR 2,000,000,000 and it is assumed that every year it will increase following the inflation assumption of 3.5%. This investment will get a return on capital in the 7th year the business is run and experience a Break Even Point in the 7th year so this investment is said to be DESERVE.